Locked‐in Biomimetic Surface Gradients that are Tunable in Size, Density and Functionalization. Issue 16 (12th August 2014) - Krabbenborg, Sven O.; van Weerd, Jasper; Karperien, Marcel; Jonkheijm, Pascal; Huskens, Jurriaan
Abstract Tuneable and stable surface‐chemical gradients in supported lipid bilayers (SLBs) hold great promise for a range of applications in biological sensing and screening. Yet, until now, no method has been reported that provides temporal control of SLB gradients. Herein we report on the development of locked‐in SLB gradients that can be tuned in space, time and density by applying a process to control lipid phase behaviour, electric field and temperature. Stable gradients of charged Texas‐Red‐, serine‐ or biotin‐terminated lipids have been prepared. For example, the Texas‐Red surface density was varied from 0 to 2 mol %, while the length was varied between several tens to several hundreds of microns. At room temperature the gradients are shown to be stable up to 24 h, while at 60 °C the gradients could be erased in 30 min. Covalent and non‐covalent chemical modification of the gradients is demonstrated, for example, by FITC, hexahistidine‐tagged proteins, and SAv/biotin. The amenability to various (bio)chemistries paves the way for novel SLB‐based gradients, useful in sensing, high‐throughput screening and for understanding dynamic biological processes.